2007
DOI: 10.1128/jb.01586-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Transcriptional Activity of the Cryptic Plasmid pRN1 fromSulfolobus islandicusREN1H1 and Regulation of Its Replication Operon

Abstract: The plasmid pRN1 from Sulfolobus islandicus REN1H1 belongs to the crenarchaeal plasmid family pRN. The plasmids in this family encode three conserved proteins that participate in plasmid replication and copy number regulation, as suggested by biochemical characterization of the recombinant proteins. In order to deepen our understanding of the molecular biology of these plasmids, we investigated the transcriptional activity of the model plasmid pRN1. We detected five major transcripts present at about 2 to 15 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Therefore, we cannot rule out the possibilities that additional transcripts may exist and that the longest version of T5 transcript represents only a minor fraction of the mRNA produced. Classical Northern experiments are commonly used to estimate both the size and relative abundance of major transcripts but are not reliable to detect transcripts of low abundance (7). Indeed, initial experiments to detect PAV1 transcripts by Northern analysis gave very weak and nonreproducible hybridization signals (not shown) probably because of the very low level of PAV1 transcripts under the culture conditions tested.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot rule out the possibilities that additional transcripts may exist and that the longest version of T5 transcript represents only a minor fraction of the mRNA produced. Classical Northern experiments are commonly used to estimate both the size and relative abundance of major transcripts but are not reliable to detect transcripts of low abundance (7). Indeed, initial experiments to detect PAV1 transcripts by Northern analysis gave very weak and nonreproducible hybridization signals (not shown) probably because of the very low level of PAV1 transcripts under the culture conditions tested.…”
Section: Discussionmentioning
confidence: 99%
“…ORF56 assembles as a tetramer on its target binding site [5]. In addition, reporter gene experiments suggested that ORF56 acts as a repressor [6]. Since the genes orf56 and orf904 are co-transcribed and the latter gene encodes the replication protein, this type of negative-feedback control could be part of the copy-control mechanism of the plasmid.…”
Section: Biochemical Characterization Of the Three Conserved Proteinsmentioning
confidence: 97%
“…As a result, ten genomes of S. islandicus strains have been sequenced, eight from the U.S. DOE (Department of Energy) Joint Genome Institute (http://www.jgi.doe.gov/genomeprojects/) and two from the joint efforts of Danish, Chinese and French laboratories. Furthermore, many genetic elements including diverse viruses and plasmids have been isolated from S. islandicus and characterized [6][7][8][9][10][11][12][13][14], providing useful tools for studying molecular biology with this model.…”
Section: Introductionmentioning
confidence: 99%